การสร้างวาทกรรมออนไลน์เกี่ยวกับสตรีมุสลิม - สาธิยา หมานเรือง (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This research aims 1) to study the process of online a discourse construction and 2) to find Muslim women images from an online discourse. This research use qualitative research methodology to analyze content of two Muslim women websites, including in-depth interview of two webmasters. The analytical frameworks are base on critical discourse analysis, Muslim women concept, computer-mediated communication, and images concept. The results of this research are these following: 1) Construction of online discourses on Muslim women are based on Thai Muslim social context ; some Muslim people are lack of Islamic knowledge and understanding, they cannot practice in Islamic way, and also west expertise and media criticize some Islamic doctrines about Muslim women in negative way. Therefore, two Muslim women websites that are www.muslimahtoday.net which is created by group of Thai Muslim students and www.baanmuslimah.com which is created by a Muslim wife house present discourses on Muslim women through internet media. In constructing online discourses, the webmasters select issues which are presented by Thai or foreign Muslim expertise and Thai Muslim people. Contents refer to the Islamic doctrine from The Holy Quran and Sunnah (practices of the Prophet Muhammad (peace be upon him)). There are two types of issues; issues about only Muslim women such as principles about practice of Muslim women in daily life and the issues about Islamic faith and practices of Muslim not only about Muslim women. 2) Images of Muslim women which are presented through the discourses on websites is the ideal images of women from Islamic doctrine; Quran and Sunnah (the practice of the prophet Muhammad). In www.muslimahtoday.net, they present Muslim women who practice in Islamic doctrines about Muslim women and the women who understand in their role. In www.baanmuslimah.com, they also present the images of women who practice in Islamic doctrines about Muslim women, who understand in their rights and role, and they also understand that they are created differently from men